Tracing the Blockchain Challenges in Healthcare: A Topic Modeling and Bibliometric Analysis - Mohammad Mehraeen; Laya Mahmoudi (Blockchain in Healthcare Today)
The application of blockchain technology to healthcare offers promise in providing solutions to some key challenges related to data sharing, privacy, security, and access control. There are however several barriers preventing blockchain adoption from spreading widely, which has prompted research efforts. This study aims to conduct a bibliometric analysis of 196 documents, indexed in the Scopus database, to examine the structure, impact, contributors, and journals. Also, topic modeling is applied to give new knowledge on the latent topical structure of this literature. As a result, five critical challenges have been identified regarding the use of blockchain in healthcare including data privacy/security, scalability, governance, interoperability and standards, and cost.